The Latest Advancements: A Comprehensive Review of Microballoons for Enhanced Gastroretention - Chavan, Payal B.; Malpure, Prashant S.; Talele, Gokul S.; Kadam, Abhishek R. (Asian Journal of Pharmaceutical Research and Development, 2024)
Because of their potential to remain in the gastric region for extended periods of time, gastro-retentive drug delivery methods hold great promise in oral treatment. This improves medication solubility, resulting in increased bioavailability and decreased drug waste. To achieve gastro-retentive qualities, various ways have been proposed, with microballoons in the form of hollow microspheres being a commonly investigated possibility. These microballoons, which are hollow spherical particles with no central core and have a size of less than 200 micrometers, provide an excellent method of managing medication release with site-specific absorption. Floating microballoons release via gastro-retentive mechanisms, effectively increasing bioavailability and providing a viable remedy for stomach retention. Hollow microspheres with optimized properties have the potential to revolutionize new drug delivery, particularly for secure, targeted, and efficient in vivo delivery. They represent a promising approach to gastric retention, reducing variability in plasma drug concentrations. This review provides insights into recent advances in formulation methods, evaluation techniques, the use of polymers in microballoons, and their applications as gastro-retentive drug delivery systems with controlled release capabilities.